(5x+7)(7x+7)=

Simple and best practice solution for (5x+7)(7x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+7)(7x+7)= equation:



(5x+7)(7x+7)=
We move all terms to the left:
(5x+7)(7x+7)-()=0
We add all the numbers together, and all the variables
(5x+7)(7x+7)=0
We multiply parentheses ..
(+35x^2+35x+49x+49)=0
We get rid of parentheses
35x^2+35x+49x+49=0
We add all the numbers together, and all the variables
35x^2+84x+49=0
a = 35; b = 84; c = +49;
Δ = b2-4ac
Δ = 842-4·35·49
Δ = 196
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{196}=14$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(84)-14}{2*35}=\frac{-98}{70} =-1+2/5 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(84)+14}{2*35}=\frac{-70}{70} =-1 $

See similar equations:

| 15r+3=7r+11 | | 125=5x^2+35 | | 2(4x+5)=2x+1 | | -8(5x-6)=-272 | | -3(2x-10)=-8 | | 0.3x+7=23 | | (6-5x)-8=-272 | | 36+5x=−3(x+4) | | –19r+1+14r=–7r–17 | | 15/20=x/39 | | √x+8+√x=4 | | 20xx=15x39 | | 3+0.5x=13-0.75x | | x-2.4=-1 | | 5(8s+4)=s+20 | | x-1=1.75 | | 3x+6=7x–10 | | 11(4v+1)=5v+11 | | x-7.1=-8.4 | | 2.5x-3.5=5.25 | | 6b-b=225÷5 | | 3(3y/4+7/4)-2y=4 | | 3•(3y/4+7/4)-2y=4 | | 0.7x=-3.5* | | (3x+1)/(4x-3)=0 | | 32=0.75/x | | x-1/3-x-2/4=1 | | m=6=-4 | | X/72=97/x | | 14=11+w/48 | | x+55=x+125 | | b-1/3=1/2 |

Equations solver categories